(3bGHdjI YQV GdfRGY Ydi GdJMcje (B/ s - (3CMeO GdSjO eMeO SYO GdMOjOis; (3Ydi bGSe s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3GdJMcje GdJLGQi GdOhdi ef Gge GdhSGFjd GdeSJNOeI dJShjI GdefGRYGJ ai GdYGde h NGUI ai eUQ MjK GQJHW GROjGO XghQg ai eUQ HGdGfaJGM GdGbJUGOi h bO JfGhdfG ai gPG GdHMK YQV eOi bGHdjI YQV GdfRGY ddJMce MjK Gf gfGc HYO GdOhd GdJi hSYJ ef fWGb bGHdjI YQV GdfRGY ddJMce HjfeG VjbJ Ohd GNQi ef gPG GdfWGb hbO aQbfG Hjf GdeSGFd GdJi jLhR GdJMce ajgG agi LejY GdeSGFd GjG cGf WHjYJgG Ohf GdeSGFd GdeJYdbI HGdfXGe GdYGe hGdeSGFd GdeJYdbI HGdGMhGd GdTNUjI adG jLhR GdGfaGb Ydi JShjI GdfRGYGJ GdeJYdbI HgG Yf WQjb GdJMcje ceG GhVMfG Gfg ai MGdI JShjI GdfRGYGJ GdeJYdbI HGdfXGe GdYGe hGdGMhGd GdTNUjI Yf WQjb GdJMcje jchf Mce GdJMcje HGWdG HGdGVGaI Gdi GMbjI GdeMceI GdeWdhH efgG GdJfajP Gf JQaV JfajP Pdc GdMces
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2010s
(3HHdjhLQGajG(B: (3UaMGJ (B138-144s
Keywords: (3GdbGfhf GdJLGQjs; (3fWGb GJaGb GdJMcjes; (3GdeSGFd GdJi jLhR GdJMcje ajgGs; (3GdeSGFd GdJi dG jLhR GdJMcje ajgG s; (3GdJMcje h GdefGRYGJs; (3HWdGf GJaGb GdJMcjes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs